Implementing the Teaching Factory Approach: Curriculum Management at MAN 2 Bantul, Yogyakarta Indonesia - Friska, Friska Mawaddah; Nora Saiva Jannana (Journal of Islamic Education Management Research, 2023)
Purpose  – This research aims to explore the implementation of curriculum management in skill-based subjects using the modified teaching factory approach at MAN 2 Bantul. The study examines the planning, development, and execution of curriculum management in the context of skill-based programs. Design/methods/approach  – Conducted as a qualitative study, this research utilizes a case study approach to delve into the intricacies of curriculum management. Data collection techniques include observation, in-depth interviews, and documentation. Analysis methods involve transcript analysis, coding/labeling, grouping, comparing and contrasting, and interpretation. Data validation employs triangulation, considering multiple sources, techniques, and periods. Findings  – The findings of this research indicate several vital points: 1) Curriculum management planning in the skills program is aligned with the institution's vision, mission, and objectives. 2) Curriculum development is tailored to students' needs and the educational institution's capabilities. 3) Implementing curriculum management in the skills program involves using the modified teaching factory method with block system learning strategies. 4) Evaluation stages include both learning and curriculum evaluations. 5) Challenges the institution faces in implementing skill programs include the novelty of the learning model, aligning existing skill programs with community needs, a shortage of educators in skill programs, marketing products, and addressing student issues. Research implications/limitations  – The impact of this research extends to educational policymakers and practitioners, providing insights into effective curriculum management for skill-based programs. Rules include the specific context of MAN 2 Bantul and the challenges faced by the institution. Practical implications  – The study offers valuable insights for educational institutions implementing skill-based programs using the modified teaching factory approach. The findings highlight effective strategies and potential challenges institutions may encounter during implementation. Originality/value  – This research contributes to the literature by examining curriculum management in skill-based programs, explicitly using the modified teaching factory method. The study's originality lies in its comprehensive analysis of the planning, development, and implementation phases, providing valuable lessons for institutions seeking innovative approaches to curriculum management in skills education.